PENDALAMAN MATERI KAS KECIL BAGI SISWA/I SMA XY - Wijoyo, Amin; Woen, Esperansya Desmonda; Lioe, Nathaniel Edbert (Jurnal Serina Abdimas, 2024)
Education about petty cash for students at SMA XY serves as an integral part of Community Service, a collaborative effort between professors and students from Tarumanagara University aimed at fostering a positive impact on Indonesia's education landscape. This initiative specifically focuses on enhancing students' knowledge of recording petty cash and related transactions within an accounting period. The comprehensive program, executed in person at SMA XY on October 11, 2023, engaged 60 students from the school. The significance of this endeavor lies in its dual contribution of providing practical insights into petty cash journaling and broadening students' overall understanding of accounting principles. The activities encompass theoretical discussions on cash concepts, methodologies for petty cash journaling, and hands-on exercises to ensure a thorough comprehension of the subject matter. This immersion in accounting fundamentals is envisioned to equip SMA XY students with the necessary skills for the challenges of higher education and future professional endeavors. As a measure of success, at the culmination of the community service, an impressive 79% of SMA XY students demonstrated their deep understanding of the Petty Cash module by correctly answering the Quizizz question bank. This outcome serves as a testament to the efficacy of the program in fostering substantial learning outcomes among the participating students.